set cR = center R;
set ccR = the carrier of ();
set ccs = the carrier of R;
set lm = the multF of R | [: the carrier of (), the carrier of R:];
A1: the carrier of () c= the carrier of R by Th16;
A2: dom the multF of R = [: the carrier of R, the carrier of R:] by FUNCT_2:def 1;
[: the carrier of (), the carrier of R:] c= [: the carrier of R, the carrier of R:]
proof
let x be object ; :: according to TARSKI:def 3 :: thesis: ( not x in [: the carrier of (), the carrier of R:] or x in [: the carrier of R, the carrier of R:] )
assume x in [: the carrier of (), the carrier of R:] ; :: thesis: x in [: the carrier of R, the carrier of R:]
then ex x1, x2 being object st
( x1 in the carrier of () & x2 in the carrier of R & x = [x1,x2] ) by ZFMISC_1:def 2;
hence x in [: the carrier of R, the carrier of R:] by ; :: thesis: verum
end;
then A3: dom ( the multF of R | [: the carrier of (), the carrier of R:]) = [: the carrier of (), the carrier of R:] by ;
now :: thesis: for x being object st x in [: the carrier of (), the carrier of R:] holds
( the multF of R | [: the carrier of (), the carrier of R:]) . x in the carrier of R
let x be object ; :: thesis: ( x in [: the carrier of (), the carrier of R:] implies ( the multF of R | [: the carrier of (), the carrier of R:]) . x in the carrier of R )
assume A4: x in [: the carrier of (), the carrier of R:] ; :: thesis: ( the multF of R | [: the carrier of (), the carrier of R:]) . x in the carrier of R
then consider x1, x2 being object such that
A5: x1 in the carrier of () and
A6: x2 in the carrier of R and
A7: x = [x1,x2] by ZFMISC_1:def 2;
reconsider x1 = x1 as Element of R by A1, A5;
reconsider x2 = x2 as Element of R by A6;
( the multF of R | [: the carrier of (), the carrier of R:]) . x = x1 * x2 by ;
hence ( the multF of R | [: the carrier of (), the carrier of R:]) . x in the carrier of R ; :: thesis: verum
end;
then reconsider lm = the multF of R | [: the carrier of (), the carrier of R:] as Function of [: the carrier of (), the carrier of R:], the carrier of R by ;
set Vos = ModuleStr(# the carrier of R, the addF of R,(0. R),lm #);
set cV = the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #);
A8: ( ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is vector-distributive & ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-distributive & ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-associative & ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-unital )
proof
A9: the multF of () = the multF of R || the carrier of () by Def4;
A10: the addF of () = the addF of R || the carrier of () by Def4;
thus ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is vector-distributive :: thesis: ( ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-distributive & ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-associative & ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-unital )
proof
let x be Element of the carrier of (); :: according to VECTSP_1:def 13 :: thesis: for b1, b2 being Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) holds x * (b1 + b2) = (x * b1) + (x * b2)
let v, w be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: thesis: x * (v + w) = (x * v) + (x * w)
reconsider xx = x as Element of R by A1;
reconsider vv = v, ww = w as Element of R ;
A11: [x,w] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A12: [x,(v + w)] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A13: [x,v] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
thus x * (v + w) = xx * (vv + ww) by
.= (xx * vv) + (xx * ww) by VECTSP_1:def 2
.= the addF of R . [(x * v),( the multF of R . [xx,ww])] by
.= (x * v) + (x * w) by ; :: thesis: verum
end;
thus ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-distributive :: thesis: ( ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-associative & ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-unital )
proof
let x, y be Element of the carrier of (); :: according to VECTSP_1:def 14 :: thesis: for b1 being Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) holds (x + y) * b1 = (x * b1) + (y * b1)
let v be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: thesis: (x + y) * v = (x * v) + (y * v)
reconsider xx = x, yy = y as Element of R by A1;
reconsider vv = v as Element of R ;
A14: [y,v] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A15: [x,v] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A16: [(x + y),v] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A17: [x,y] in [: the carrier of (), the carrier of ():] by ZFMISC_1:def 2;
thus (x + y) * v = the multF of R . [( the addF of () . [x,y]),vv] by
.= (xx + yy) * vv by
.= (xx * vv) + (yy * vv) by VECTSP_1:def 3
.= the addF of R . [(x * v),( the multF of R . [yy,vv])] by
.= (x * v) + (y * v) by ; :: thesis: verum
end;
thus ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-associative :: thesis: ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is scalar-unital
proof
let x, y be Element of the carrier of (); :: according to VECTSP_1:def 15 :: thesis: for b1 being Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) holds (x * y) * b1 = x * (y * b1)
let v be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: thesis: (x * y) * v = x * (y * v)
reconsider xx = x, yy = y as Element of R by A1;
reconsider vv = v as Element of R ;
A18: [x,(y * v)] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A19: [y,v] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A20: [(x * y),v] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
A21: [x,y] in [: the carrier of (), the carrier of ():] by ZFMISC_1:def 2;
thus (x * y) * v = the multF of R . [( the multF of () . (x,y)),vv] by
.= (xx * yy) * vv by
.= xx * (yy * vv) by GROUP_1:def 3
.= the multF of R . [xx,(lm . (y,v))] by
.= x * (y * v) by ; :: thesis: verum
end;
let v be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: according to VECTSP_1:def 16 :: thesis: (1. ()) * v = v
reconsider vv = v as Element of R ;
1_ R in center R by Th19;
then 1_ R in the carrier of () ;
then A22: [(1_ R),vv] in [: the carrier of (), the carrier of R:] by ZFMISC_1:def 2;
thus (1. ()) * v = lm . ((1. R),vv) by Def4
.= (1. R) * vv by
.= v ; :: thesis: verum
end;
A23: ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is add-associative
proof
let u, v, w be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: according to RLVECT_1:def 3 :: thesis: (u + v) + w = u + (v + w)
reconsider uu = u, vv = v, ww = w as Element of the carrier of R ;
thus (u + v) + w = (uu + vv) + ww
.= uu + (vv + ww) by RLVECT_1:def 3
.= u + (v + w) ; :: thesis: verum
end;
A24: ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is right_zeroed
proof
let v be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: according to RLVECT_1:def 4 :: thesis: v + (0. ModuleStr(# the carrier of R, the addF of R,(0. R),lm #)) = v
reconsider vv = v as Element of the carrier of R ;
thus v + (0. ModuleStr(# the carrier of R, the addF of R,(0. R),lm #)) = vv + (0. R)
.= v by RLVECT_1:def 4 ; :: thesis: verum
end;
A25: ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is right_complementable
proof
let v be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: according to ALGSTR_0:def 16 :: thesis:
reconsider vv = v as Element of the carrier of R ;
consider ww being Element of the carrier of R such that
A26: vv + ww = 0. R by ALGSTR_0:def 11;
reconsider w = ww as Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) ;
v + w = 0. ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) by A26;
hence ex w being Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) st v + w = 0. ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) ; :: according to ALGSTR_0:def 11 :: thesis: verum
end;
ModuleStr(# the carrier of R, the addF of R,(0. R),lm #) is Abelian
proof
let v, w be Element of the carrier of ModuleStr(# the carrier of R, the addF of R,(0. R),lm #); :: according to RLVECT_1:def 2 :: thesis: v + w = w + v
reconsider vv = v, ww = w as Element of the carrier of R ;
thus v + w = ww + vv by RLVECT_1:2
.= w + v ; :: thesis: verum
end;
hence ex b1 being strict VectSp of center R st
( addLoopStr(# the carrier of b1, the addF of b1, the ZeroF of b1 #) = addLoopStr(# the carrier of R, the addF of R, the ZeroF of R #) & the lmult of b1 = the multF of R | [: the carrier of (), the carrier of R:] ) by A8, A23, A24, A25; :: thesis: verum